DIACHRONIC CHANGES IN LONG-BONE DIMENSIONS AND RECONSTRUCTED STATURE FROM THE EARLY IRON AGE TO THE EARLY MEDIEVAL PERIOD: EVIDENCE FROM THE ZAYUKOVO-3 CEMETERY (KABARDINO-BALKARIA) - Perevozcikova, Alla Aleksandrovna; Goncarova, Natalia Nikolaevna; Berezina, Natalia Akovlevna (History, Archeology and Ethnography of the Caucasus, 2025)
This study investigates changes in skeletal long-bone dimensions in North Caucasus populations over a span of approximately 1,500 years (from 8th century BC to 7th century AD), using materials from the Zayukovo-3 polycultural cemetery (Kabardino-Balkaria Republic, Russia) as a case study. The research aims to reconstruct stature and assess morphological variability among individuals from three key cultural-chronological phases of the site: the Western Koban culture of the pre-Scythian period (8th–5th centuries BC), the Podkumok-Khumara cultural group of the Late Sarmatian period (1st–3rd centuries AD), and the Early Alanian period (5th–7th centuries AD). Methods employed include paleoanthropological analysis, reconstruction of fragmented skeletal remains, osteometric measurement, stature estimation, and statistical processing of the resulting data. The analysis revealed statistically significant differences and similarities among the compared groups. Males from the Koban and Alanian stages displayed morphological similarity, while female stature showed no significant difference between the Koban and Sarmatian samples. The Koban population exhibited pronounced sexual dimorphism in skeletal proportions. Sarmatian males had the lowest mean stature (163 cm) and were morphologically distinct from the other groups. Reconstructed stature was 169 cm for Koban males and 168 cm for Alanian males. These results align with recent paleogenetic studies suggesting biological continuity between Koban and Alanian populations. The findings underscore the value of osteometric analysis in paleoanthropological research and highlight the complex biological dynamics of ancient North Caucasus populations. They indicate both long-term continuity across certain archaeological cultures and the potential impact of external components during the Sarmatian period. These patterns warrant further verification through interdisciplinary studies.
Keywords: West Koban archeological culture; Late Sarmatian period (Podkumok-Khumara-type monuments); Alans; North Caucasus; Early Iron Age; Middle Ages; stature reconstruction; morphological variability; biological anthropology